Toward the Treatment of Inherited Diseases of the Retina Using CRISPR-Based Gene Editing - Hernández-Juárez, Jennifer; Rodríguez-Uribe, Genaro; Borooah, Shyamanga (Frontiers in Medicine, 2021)
Inherited retinal dystrophies [IRDs] are a common cause of severe vision loss resulting from pathogenic genetic variants. The eye is an attractive target organ for testing clinical translational approaches in inherited diseases. This has been demonstrated by the approval of the first gene supplementation therapy to treat an autosomal recessive IRD, RPE65-linked Leber congenital amaurosis (type 2), 4 years ago. However, not all diseases are amenable for treatment using gene supplementation therapy, highlighting the need for alternative strategies to overcome the limitations of this supplementation therapeutic modality. Gene editing has become of increasing interest with the discovery of the CRISPR-Cas9 platform. CRISPR-Cas9 offers several advantages over previous gene editing technologies as it facilitates targeted gene editing in an efficient, specific, and modifiable manner. Progress with CRISPR-Cas9 research now means that gene editing is a feasible strategy for the treatment of IRDs. This review will focus on the background of CRISPR-Cas9 and will stress the differences between gene editing using CRISPR-Cas9 and traditional gene supplementation therapy. Additionally, we will review research that has led to the first CRISPR-Cas9 trial for the treatment of CEP290-linked Leber congenital amaurosis (type 10), as well as outline future directions for CRISPR-Cas9 technology in the treatment of IRDs.